2014
DOI: 10.3111/13696998.2014.893241
|View full text |Cite
|
Sign up to set email alerts
|

Switching of biologic disease modifying anti-rheumatic drugs in patients with rheumatoid arthritis in a real world setting

Abstract: Monthly total healthcare costs were higher for bDMARD switchers following the switch compared to non-switchers. Patients on abatacept switched less frequently than patients on anti-TNFs. This study highlights the need to identify patients who are likely to switch in order to ensure they receive the appropriate therapy which may improve outcomes and decrease healthcare costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 12 publications
4
27
0
Order By: Relevance
“…These results complement a recent US administrative claims data analysis that showed that patients who switched biologic incurred higher costs than patients who did not switch (USD 3,759 vs USD 2,343 per month; P <0.05) 36. Furthermore a recent Swedish study showed that patients who were nonpersistent incurred USD 1,730 higher costs per year compared to persistent patients 37.…”
Section: Discussionsupporting
confidence: 81%
“…These results complement a recent US administrative claims data analysis that showed that patients who switched biologic incurred higher costs than patients who did not switch (USD 3,759 vs USD 2,343 per month; P <0.05) 36. Furthermore a recent Swedish study showed that patients who were nonpersistent incurred USD 1,730 higher costs per year compared to persistent patients 37.…”
Section: Discussionsupporting
confidence: 81%
“…Although therapy switch in DMARD users has been shown to be frequent (Meissner et al. ; Jørgensen et al. ), the treatment regimen (switch, concurrent use) could not be assessed due to the cross‐sectional study design per calendar year.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, direct linkage between prescriptions and diagnoses of possible indications is not possible. Although therapy switch in DMARD users has been shown to be frequent (Meissner et al 2014;Jørgensen et al 2015), the treatment regimen (switch, concurrent use) could not be assessed due to the cross-sectional study design per calendar year.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, monthly total healthcare costs have been shown to be higher for patients with RA who switch therapy than those who do not, and higher again for a second or third switch. 18 Here, we aim to provide an evaluation of treatment patterns, associated healthcare resource use (HCRU), and costs for patients with RA in the 12-month period following TNFi treatment initiation. In addition, we further examine overall TNFi treatment cycling patterns, HCRU, and costs in the 12month period following switch from index TNFi to another biologic DMARD (alternative TNFi or a non-TNFi biologic DMARD).…”
Section: Introductionmentioning
confidence: 99%